Addressing sleep problems and fatigue within child and adolescent mental health services: A qualitative study. (January 2020) - Higson-Sweeney, Nina; Loades, Maria Elizabeth; Hiller, Rachel; Read, Rebecca
Background: Both fatigue and sleep difficulties are common symptoms of mental health presentations such as depression and anxiety. Despite this, little is known about how psychologists in Child and Adolescent Mental Health Services (CAMHS) assess and treat these common symptoms. Method: Qualitative interviews with nine psychologists working in CAMHS analysed using thematic analysis. Results: Fatigue and sleep problems do not tend to be the focus of assessment because they are seen to be part of other presentations and not accorded priority. Psychologists struggled to differentiate fatigue from sleep problems, with greater clarity about sleep problems, which appear to be more routinely assessed. A number of barriers to addressing fatigue and sleep problems were identified, including lack of motivation from young people to make behavioural changes to address fatigue and/or sleep difficulties. Psychologists wished for more training, access to information for young people and families and more service integration with paediatric physical health settings. Conclusion: Sleep problems and fatigue may not be thoroughly assessed and addressed in CAMHS and are often conflated, with the focus on enquiring about sleep, not fatigue. Further research is required to elucidate whether the themes identified are more pervasive. Potential interventions include training and information provision.